Platelet-rich plasma injections for the treatment of hamstring injuries: a randomized controlled trial - Hamid, M.S.A.; Mohamed Ali, M.R.; Yusof, A.; George, J.; Lee, P.C. (SAGE Publications (UK and US), 2014)
Background: A hamstring injury is one of the most common types of injury affecting athletes. Despite this, the optimal management of hamstring muscle injuries is not yet defined. The effect of autologous platelet-rich plasma (PRP) therapy on the recovery of hamstring injuries is unclear.